2006
DOI: 10.1242/dev.02250
|View full text |Cite
|
Sign up to set email alerts
|

Crossveinless 2 is an essential positive feedback regulator of Bmp signaling during zebrafish gastrulation

Abstract: Signaling by bone morphogenetic proteins (Bmps) plays a pivotal role in developmental and pathological processes, and is regulated by a complex interplay with secreted Bmp binding factors, including Crossveinless 2 (Cvl2). Although structurally related to the Bmp antagonist Chordin, Crossveinless 2 has been described to be both a Bmp agonist and antagonist. Here, we present the first loss-of-function study of a vertebrate cvl2 homologue, showing that zebrafish cvl2 is required in a positive feedback loop to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
197
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(220 citation statements)
references
References 68 publications
18
197
5
Order By: Relevance
“…CV2-VWC1 bound to BMP-2/-7 and GDF-5 with affinities similar to those of full-length CV2 (Fig. 1B) (24). The VWC domains 2, 3, 4, and 5 and the fragment VWC2-5 had no binding affinity for these ligands (data not shown and Fig.…”
Section: Binding Affinities and Specificities Of Bmps For Modulatormentioning
confidence: 69%
See 2 more Smart Citations
“…CV2-VWC1 bound to BMP-2/-7 and GDF-5 with affinities similar to those of full-length CV2 (Fig. 1B) (24). The VWC domains 2, 3, 4, and 5 and the fragment VWC2-5 had no binding affinity for these ligands (data not shown and Fig.…”
Section: Binding Affinities and Specificities Of Bmps For Modulatormentioning
confidence: 69%
“…These results are consistent with our observation that excessive doses of CV2 inhibited BMP-2-induced ALP activity. However, in vivo studies showed that CV2 is an essential pro-BMP regulator of BMP signaling during zebrafish gastrulation (24) and in mouse organogenesis (26). Although the mechanism of the in vivo pro-BMP activity of CV2 remains uncertain, a model for positive feedback is intriguing (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kielin/Chordin-like protein (Kcp) with 18 Chordin-like CR domains, one thrombospondin domain (Tsp), and one von Willebrand factor D (vWF-D) domain enhances BMP signaling (13). Crossveinless-2 with five Chordin-like CR domains and one vWF-D domain is a BMP agonist/antagonist (14,15). Connectivetissue growth factor, which has four structural domains including the Chordin-like CR domain, insulin-like growth factor domain, Tsp domain, and C-terminal knot, modulates BMP signaling and TGFb signaling negatively and positively, respectively (16).…”
Section: Introductionmentioning
confidence: 99%
“…Modulator proteins of the chordin family present a unique exception to this inhibitory-only function in that they exhibit two contrary activities (Larrain et al, 2001). Depending on the cellular context, chordin and another family member, crossveinless 2 (CV2), can either down-regulate BMP signalling (anti-BMP activity) or enhance BMP signalling (pro-BMP activity) (Binnerts et al, 2004;Ikeya et al, 2006;Rentzsch et al, 2006). The molecular mechanism of this switch in the regulatory mechanism is so far unknown.…”
Section: Introductionmentioning
confidence: 99%